Pengelolaan Keuangan bagi UMKM pada Kelurahan Balang Baru, Kecamatan Tamalate - Hajrah Hamzah; Hanisyahputra, Farhan Dwinanda; Kartika Septiary Pratiwi Musa; Warka Syachbrani; Andi Muh Syukur Hidayatullah (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
This Community Partnership Program (PKM) was implemented to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Balang Baru Subdistrict, Tamalate District, Makassar City, particularly in financial management. The main problems faced by local MSME actors include low financial literacy and the absence of systematic and sustainable financial recording practices, which hinder optimal business performance evaluation. Through this program, a team from Universitas Negeri Makassar designed and carried out training and mentoring activities focused on the use of digital financial recording systems that are user-friendly for MSME actors. The activities included the preparation of training materials on basic financial management, hands-on practice in preparing simple financial statements, the use of digital bookkeeping applications, and an evaluation of their implementation. The training was conducted intensively over three days using interactive and practical methods. The results showed a significant improvement in participants’ understanding and skills in managing business finances, recording transactions in an organized manner, and preparing financial reports that could be used for basic business analysis. Moreover, the program encouraged MSME actors to become more independent in making data-driven business decisions. This initiative is expected to have a long-term impact in promoting professionalism among MSMEs and serve as a replicable model for community empowerment through improved financial literacy.